Sustainability governance and legitimisation processes: Gulf of Mexico oil spill - Nader Elsayed (18060043) (2020)
Purpose The purpose of this paper is to explore the emergence of sustainability governance through the unfolding hybridisation process between corporate governance and corporate social responsibility and the implications of this for understanding patterns in sustainability reporting over time. Design/methodology/approach The Gulf of Mexico oil spill incident is an extreme case study undertaken to examine its implications on the organisational legitimacy of British Petroleum (BP) and the latter’s response to the incident and beyond. The paper draws on Suchman’s legitimacy framework (1995) to understand sustainability governance as an organisational practice that evolved post the Gulf of Mexico oil spill to manage BP’s legitimacy. It draws on archival records and documentation from 2008 to 2017, as key sources for data collection, using interrogation by NVivo software. Findings Sustainability governance is a sound practice that was socially constructed to manage the re-legitimatisation process following the Gulf of Mexico oil spill. It is characterised by broadness (the interplay between the corporate governance and corporate social responsibility disciplines), dynamic (developing the tactics to repair and maintain legitimacy), agility (conforming to the accountability for socially responsible investment and ensuring steps towards geopolitically responsible investment) and interdependence (reflecting composition and interactions). Practical implications This paper has practical implications for organisations, in terms of sustainability governance’s constitution, mechanism and characteristics. Social implications This paper has implications not only for organisations, in terms of sustainability governance’s characteristics, but also for policy-makers, regulators and accounting education. However, the present paper’s insights are achieved through an in-depth and longitudinal case study. Originality/value This paper has problematized the concept of sustainability governance and elaborated its evolution (the emergence, enactment, deployment and interplay) process. The sustainability governance showed an otherwise organisational response that moves our understanding of the deployment of disclosure for complex organisational change as a way to discredit events. Other Information Published in: Sustainability Accounting, Management and Policy Journal License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1108/sampj-09-2018-0242